(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Due to the increasing demand of services and content, Quality of Service (QoS) has become an important aspect in digital broadcasting industry especially with the implementation of Digital Terrestrial Television (DTT) in Malaysia. Thus, the performance of DVB-T2 in Malaysia should be investigated because there are areas which are not in the coverage due to variety of terrain, where some areas received weak DVB-T2 signals. Apart from geological and topographic factors in Malaysia, the selection of DVB-T2 parameters is also an important factor in determining signal strength and coverage This research has proposed to study the performance analysis of DVB-T2 propagation for fixed reception in Malaysia’s central region. The Field Strength Measurement (FSM) was set up to evaluate the QoS of DVB-T2 signal such as Field Strength (E), Modulation Error Ratio (MER), and Carrier to Noise Ratio (C/N) at specific test points across Malaysia’s central region. The FSM was simulated at the designated test points using CHIRplus_BC software to evaluate the performance of Single Frequency Network (SFN) at three locations of transmitter. The DVB-T2 Modulation and Forward Error Correction (FEC) code rate parameters were simulated in order to evaluate the improvement in terms of coverage area. It can be concluded that the coverage of DTT is reduced with the increase in the distance of the measurement area to the transmitter. The finding also shows that the field strength value obtained from FSM and simulation was comparable. Furthermore, from the simulation results. it can be perceived that the coverage area across the central region of Malaysia could be improved by optimizing the modulation and FEC code rate. However, there is a trade-off between the signal coverage and channel capacity. The greater the signal coverage the less the channel capacity.